2009
DOI: 10.1111/j.1463-1326.2009.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of beta‐blockers with the renal uptake transporter OCT2

Abstract: These in vitro results demonstrate that alterations of uptake transporter function by beta-blockers have to be considered as potential mechanisms underlying drug-drug interactions in the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 11 publications
3
18
1
1
Order By: Relevance
“…Likewise, inhibitory effects against the human OCT2 transporter by PF-04971729 were weak (IC 50 Ͼ 900 M), and at the unbound systemic exposures (free C max ϭ 1.0 -11 nM) associated with efficacious daily doses of PF-04971729 (1.1-13 mg) are unlikely to cause pharmacokinetic interactions with the OCT2 substrate, metformin, a treatment of choice for T2DM (Setter et al, 2003). In the case of metformin, the principal clearance mechanism involves active renal excretion in the unchanged form, which is mediated by OCT2 (Kimura et al, 2005); modulation of this elimination mechanism through inhibition and/or genetic polymorphisms is known to result in drug-drug interactions (Bachmakov et al, 2009;Chen et al, 2009). Finally, with the involvement of multiple elimination mechanisms (e.g., CYP3A4/3A5 and CYP2D6 oxidation and UGT1A9/2B7 glucuronidation) for PF-04971729, the fraction of drug metabolized via a single clearance pathway is reduced and so is the potential for pharmacokinetic interactions involving that pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, inhibitory effects against the human OCT2 transporter by PF-04971729 were weak (IC 50 Ͼ 900 M), and at the unbound systemic exposures (free C max ϭ 1.0 -11 nM) associated with efficacious daily doses of PF-04971729 (1.1-13 mg) are unlikely to cause pharmacokinetic interactions with the OCT2 substrate, metformin, a treatment of choice for T2DM (Setter et al, 2003). In the case of metformin, the principal clearance mechanism involves active renal excretion in the unchanged form, which is mediated by OCT2 (Kimura et al, 2005); modulation of this elimination mechanism through inhibition and/or genetic polymorphisms is known to result in drug-drug interactions (Bachmakov et al, 2009;Chen et al, 2009). Finally, with the involvement of multiple elimination mechanisms (e.g., CYP3A4/3A5 and CYP2D6 oxidation and UGT1A9/2B7 glucuronidation) for PF-04971729, the fraction of drug metabolized via a single clearance pathway is reduced and so is the potential for pharmacokinetic interactions involving that pathway.…”
Section: Discussionmentioning
confidence: 99%
“…To increase assay sensitivity, the metformin concentration chosen for the inhibition study was below its reported K m value (Bachmakov et al, 2009). Thus, the uptake of metformin at the concentration of 5 M in the HEK293 cells transfected with hOCT2 is 10-fold greater than the corresponding uptake in wild-type HEK293 cells, which provides a large dynamic window to assess inhibitory potency against the cation transporter.…”
Section: Methodsmentioning
confidence: 99%
“…Vectortransfected HEK293 control cells were established by the same method using the respective expression plasmid without an insert for transfection. Singletransfected MDCK-OCT2 and MDCK-MATE1 cells as well as double-transfected MDCK-OCT2-MATE1 cells were previously established and characterized regarding protein expression, protein localization, and functionality in our laboratory (3,20).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, several endogenous compounds such as neurotransmitters, hormones, and metabolites are transported in vitro by OCTs (for review, see Koepsell et al, 2007). Drugs transported by or inhibiting all three OCTs in vitro include anesthetic drugs [e.g., ketamine and cocaine (Amphoux et al, 2006)], b-blockers [e.g., propranolol (Umehara et al, 2008;Bachmakov et al, 2009)], antidepressants [e.g., citalopram (Ahlin et al, 2008)], and oral antidiabetic drugs [e.g., metformin (Kimura et al, 2005); for detailed description of the substrate spectrum of OCT1-OCT3, see Nies et al, 2011].…”
Section: Transporter-mediated Drug Interactionsmentioning
confidence: 99%